ANALYSIS OF THE EFFICIENCY AND EFFECTIVENESS OF REGIONAL BUDGET IMPLEMENTATION IN SUBULUSSALAM CITY DEVELOPMENT PLANNING: (Case Study at Badan Perencanaan dan Pembangunan (BAPPEDA) in Subulussalam) - Angkat, Nanang Sahputra; Badli, Saiful; Yasrizal, Yasrizal (Jurnal Ilmiah Teunuleh, 2022)
The purpose of this study is to analyze the effectiveness and efficiency of the implementation of the Subulussalam City Bappeda budget to increase knowledge and insight for the author, economical in the procurement and allocation of resources, efficiency in the use of resources in the sense that their use is expected and the results are maximized, and effective in the sense of achieving the desired goals and objectives. The data analysis used is descriptive analysis. The level and criteria for implementing the subulussalam city bappeda budget for 2017 - 2021 vary greatly. The highest effectiveness rate occurred in 2019 and the lowest occurred in 2020. The implementation of the 2017, 2018, 2019, and 2021 budgets is said to be effective, but in 2010 the level of effectiveness is still lacking because the realization of the budget has a significant difference with the budget target. This activity occurred because there were several activities that were budgeted, then not implemented, and also had something to do with the kovid 19 pandemic which made the budget cut. But other activities that have been budgeted have been effective. The implementation of the subulussalam city bappeda budget in 2017 - 2021, as a whole has been processed efficiently, the implementation of the budget for 2017 to 2020, is categorized as very efficient. The implementation of the budget for 2017 - 2020, is categorized as very efficient only in 2021 it is categorized as efficient.